Recalled Childhood Gender-Related Play Behaviour and Current Gender-Related Occupational Interests in University Students: Examining the Mediating Roles of Gender Compatibility, Goal Endorsement, and Occupational Stereotype Flexibility - Kung, Karson T. F. (Frontiers in Psychology, 2022)
Substantial average gender differences in childhood play behaviour and occupational interests have been well-documented. Recent research shows that childhood gender-related play behaviour longitudinally predicts gender-related occupational interests in adolescence. The first aim of the present study was to extend this recent finding by examining whether university students’ recalled childhood gender-related play behaviour predicts their current gender-related occupational interests. The second aim of the present study was to investigate whether gender-related socio-cognitive processes mediate the relation between childhood play behaviour and subsequent occupational interests. University students (260 men, 542 women) completed scales assessing recalled childhood gender-related play behaviour, gender-related occupational interests, gender typicality, gender contentedness, agentic goal endorsement, communal goal endorsement, and gender-related occupational stereotype flexibility. In the present study, recalled childhood gender-related play behaviour predicted gender-related occupational interests in both men and women. In men, gender typicality and gender contentedness mediated the play-interests link. In women, gender typicality and communal goal endorsement mediated the play-interests link. The present study provides further evidence that childhood gender-related play behaviour is related to subsequent gender-related occupational interests. Although the current study has a correlational design, one interpretation of the current findings is that childhood play may influence socio-cognitive processes, such as gender compatibility and goal endorsement, which may in turn shape occupational interests.